DNA methylation variant, B-vitamins intake and longitudinal change in body mass index - X. Li; T. Wang; Zhao, M.; Huang, T.; Sun, D.; Han, L.; Nisa, H.; Shang, X.; Heianza, Y.; Qi, L. (Int J Obes (Lond)Int J Obes (Lond), 2018)
BACKGROUND: Growing evidence has implicated DNA methylation (DNAm) in the regulation of body adiposity; a recent epigenome-wide association study (EWAS) identified a genetic variant determining DNAm at the SREBF1 gene that affected body mass index (BMI). OBJECTIVE: In the present study, we tested interactions between DNAm variant rs752579 and methylation metabolism-related B-vitamins (folate, vitamin B2, vitamin B6, and vitamin B12) on longitudinal change in BMI in the Women's Health Initiative Memory Study (WHIMS). DESIGN: A total of 5687 white women aged 65-79 from WHIMS with genotyping data on SNP rs752579 were included in the analysis. B-vitamins intakes were estimated by a self-report semi-quantitative food frequency questionnaire. BMI was measured at baseline and 6-year follow-up. RESULT: We found significant interactions between the SREBF1 rs752579 genotype and intake of food source B-vitamins on 6-year change in BMI (p interaction <0.01 for all). BMI changes (kg/m(2)) per DNAm-increasing (C) allele were -0.29, 0.06, and 0.11 within subgroups of increasing tertiles of food source folate intake; and the corresponding BMI changes (kg/m(2)) were -0.25, -0.01, and 0.15 for vitamin B2 intake; -0.17, -0.16, and 0.21 for vitamin B6 intake; and -0.12, -0.23, and 0.26 for vitamin B12 intake, respectively. Similar gene-diet interaction patterns were observed on the change in body weight. CONCLUSIONS: Our data suggest that habitual intake of food source B-vitamins may modify the effect of DNAm-related variant on long-term adiposity change.